Типові помилки при виготовленні обмоток двообмоткових асинхронних машин - Лущик, В.Д.; Береда, І.М. (Електротехніка і електромеханіка, 2012)
Electromagnetic processes in a 4-pole winding made with two parallel
branches in each phase are considered in the presence of a 6-
polar field. Recommendations for 4-pole windings manufacturing
techniques in dual-winding asynchronous machines are given.